2009
DOI: 10.1210/jc.2009-1026
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Excess Promotes Breast Cancer Chemoresistance

Abstract: These data indicate that GH can directly induce resistance to chemotherapeutic drugs with a mechanism that might involve GH-induced early gene transcription and support the hypothesis that GH excess can hamper BC treatment, possibly resulting in an increased mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…On the other hand, a study indicated that PI3-K signaling is involved in BCRP expression and inhibiting of this pathway resulted in increased intracellular accumulation of chemotherapeutic drugs and cytotoxicity in tumor cells (28,29). We observed the effect of IGF-I on proliferation of the OVCAR3 cell line in serum-free conditions and protection of the cells from cytotoxic effects of carboplatin or taxol similarly to that observed with doxorubicin in MCF7 human breast cancer (30) and carboplatin in ovarian cancer (31). The previous reports (3234) favor a partial involvement of ABC protein (MRP2) in drug resistance with platinum derived agents.…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, a study indicated that PI3-K signaling is involved in BCRP expression and inhibiting of this pathway resulted in increased intracellular accumulation of chemotherapeutic drugs and cytotoxicity in tumor cells (28,29). We observed the effect of IGF-I on proliferation of the OVCAR3 cell line in serum-free conditions and protection of the cells from cytotoxic effects of carboplatin or taxol similarly to that observed with doxorubicin in MCF7 human breast cancer (30) and carboplatin in ovarian cancer (31). The previous reports (3234) favor a partial involvement of ABC protein (MRP2) in drug resistance with platinum derived agents.…”
Section: Discussionsupporting
confidence: 65%
“…Shield1 is a membrane permeant molecule that binds to the DD-C tag, 'shielding' the fusion protein from proteasomal degradation. Transfections were carried out as described previously [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Despite in vitro and in vivo studies have demonstrated a direct action of pegvisomant on different organs and tissues [35] and a possibile direct role in chemoresistance [36,37], data concerning direct effects of PEGV on GH secretion by pituitary adenoma are conflicting. Some studies have observed an impairment of GH autofeedback in somatotrophs [38,39], whereas other investigators have demonstrated that PEGV does not effect pituitary somatotrophs directly and it does not cross the human blood–brain barrier [40,41], thus favoring GH-secretion indirectly via IGF-I lowering.…”
Section: Discussionmentioning
confidence: 99%